An energy harvesting module for a 23kV distribution line sensor node in 65nm CMOS - Monisit, Kristofer M. (College of Engineering, University of the Philippines Diliman, 2014)
The magnetic field intensity around a 23kV distribution power line varies widely due to the varying current flow of 0 A to 530 A converted to a voltage using a transformer. A methodology is presented for designing an energy harvesting frontend for an environment where it is exposed to widely varying voltage inputs. The first part is for sizing cascaded rectifier cells to enable voltage multiplication at low input conditions. It optimizes for acceptable series voltage drop and gate capacitance, reducing leakage at the same time. Effects of pump capacitance on maintaining output DC voltage is analyzed with respect to continuous load currents. The resulting design parameters are obtained in terms of VDS drop, leakage, and gate capacitance needed to supply a continuous load current, and output capacitance needed to support a burst load current. The second part is for adjusting a basic clamp regulator topology to regulate the output DC voltage within specification in the presence of CMOS process and temperature variations. The result is a resistive divider ratio used to compensate for variations in the reference voltage, circuit modifications to ensure proper bootstrap sequence. The methodology was applied in the design of an energy harvesting frontend that operates in AC input voltages of 0.5V to 9.4V. Across that input voltage range, it is able to output a regulated DC voltage in the range of 09.V to 1.2V. It is capable of supplying worst case loads of 1.0mA continuous or 3.0mA over 3.0mA. Output regulation performance is sustained over CMOS process variations and operating temperatures of 0°C to 100°C